The impact of social capital dimensions on the structural empowerment of workers Applied research in the Directorate of the Municipality of Samawa - سعيد, سناء عبد الرحيم; ردام, اركان عبد الله (Journal of Economics and Administrative Sciences, 2018)
The purpose of the research is to identify the social capital of the Municipality of Samawah Municipality by defining the level of its three dimensions (the structural dimension, the relational dimension and the cognitive dimension) and identifying the appropriate means that contribute to increasing the structural empowerment of the workers in the Municipality of Samawah. Between the social capital and the structural empowerment of the workers. From the perspective of social capital, the researchers examined the correlation and the effect of dimensions (structural, relational, cognitive) on the structural empowerment of the workers and with data collected from a sample of (168) Samawah, which is part of the Ministry of Construction, Housing and Public Municipalities. This research was presented and analyzed the results of the research (the effect of social capital on the structural empowerment of workers), By presenting the computational environment to diagnose sample responses, standard deviations to estimate the extent of dispersion in the responses, and the coefficient of variation to determine the degree of homogeneity in the responses of the research sample at the general level of the search variables. Based on the fifth Likert scale in the responses of the sample, the response level will be limited (1 - 5) and five levels according to the categories, and the two research hypotheses on the existence of (relationship and relationship between the impact of social capital and the structural empowerment of workers), and proved the results of the application of the validity of the hypotheses that were raised, on the basis of which was formulated a set of results that Include A set of administrative practices necessary to build social capital and enhance the structural empowerment of workers. The organization, which has been characterized by having active and active networks and a deep reservoir of trust, is likely to have future interest in increasing them. Is characterized by being divided and fragmented to some extent, because it does not characterized by a network of social relations ,the main recommendations were to focus on the importance of joint work and attention to the networks of work by encouraging workers to build social relations through attention to training, working methods and informal practices. Joint work is a successful way to build a solid foundation for structural empowerment. and the value of scientific research through the guidance to use these modern concepts to access the sporadic ways in the management of government departments.